S’engager au travail et hors travail : quelles articulations entre deux registres de participation ? - Cécile Rodrigues; Étienne Penissat; Tristan Haute; Pierre Blavier (La Nouvelle Revue du Travail)
This article draws on data from an original study to explore how forms of workplace and political participation, two dimensions often studied separately, can be combined in different ways. We identify five configurations of participation, which offer a more nuanced picture than the hypotheses of cumulative practices or substitutions between practices. We also show that these configurations are characterized by different socio-professional profiles and political attitudes. While work appears to be a space of struggle between different repertoires of participation, different relationships to work influence both the levels and forms of political and workplace participation.